Metformin: old friend, new ways of action–implication of the gut microbiome?. Issue 4 (July 2018) - Rodriguez, Julie; Hiel, Sophie; Delzenne, Nathalie M.
Abstract : Purpose of review: Gut dysbiosis was recently associated with the occurrence of type 2 diabetes (T2D). In addition to this finding, an increasing number of studies performed upon the last 5 years have also shown that metformin treatment leads to changes in gut bacterial composition in diabetic patients. This review focuses on the articles describing the effects of metformin on gut homeostasis (including the gut microbiota) and proposes potential mechanisms involved in those effects. Recent findings: Several human and animal studies emphasized that metformin alters the gut microbiota composition by enhancing the growth of some bacteria, such as Akkermansia muciniphila, Escherichia spp. or Lactobacillus and by decreasing the levels of some other ones like Intestinibacter . In-vitro studies also demonstrated a direct action of metformin on the growth of A. muciniphila and Bifidobacterium adolescentis . Moreover, in the intestines, metformin does not only improve the glucose uptake, but it also promotes the short-chain fatty acid (SCFA) production, protects the intestinal barrier and regulates the secretion of gut peptides Summary: It is now clear that gut microbiota participates to the glucose-lowering effects of metformin in the context of diabetes. Further work is now needed to determine the exact mechanisms of action of the drug and to understand by which processes metformin is able to enhance the growth of some bacteria exhibiting beneficial effects for the host.